Multiple faces of stress in the zebrafish (Danio rerio) brain - Pietsch, Constanze; Konrad, Jonathan; Wernicke von Siebenthal, Elena; Pawlak, Paulina (Frontiers in Physiology, 2024)
Changing expression of certain genes as a consequence of the exposure to stressors has not been studied in detail in the fish brain. Therefore, a stress trial with zebrafish was conducted aiming at identifying relevant gene regulation pathways in different regions of the brain. As acute stressors within this trial feed rewarding, feed restriction, and air exposure have been used. The gene expression data from the experimental fish brains have been analyzed by means of Principal Component Analyses (PCA) whereby the individual genes have been compiled according to the regulation pathways in the brain. The results did not indicate a mutual response across treatment groups and gender groups. To evaluate if a similar sample structure belonging to a high sample size would have allowed a classification of the gene expression patterns according to the treatments, the data have been bootstrapped and used for building Random Forest models. These revealed a high accuracy of the classifications, but different genes in females and males contributed to the classification algorithms the most. These analyses showed that less than 8 genes are in most cases sufficient for an accurate classification. Moreover, mainly genes belonging to the stress axis, to the isotocin regulation pathways or to serotonergic pathways had the strongest influence on the outcome of the classification models.